Conclusions [In The political economy of agricultural policy reform in India] - Birner, Regina; Gupta, Surupa; Sharma, Neeru (International Food Policy Research Institute, 2011)
This monograph has analyzed why so few political solutions to the problems of fertilizer supply and to the "electricity-groundwater conundrum" have emerged after more than a decade of reform efforts. With regard to fertilizer supply, the study concentrated on why the GoI has not been able to reduce or better target the fertilizer subsidy despite several attempts. The study shows that the ability to raise farmgate prices is constrained by coalition politics and by political representatives of owners of medium-sized and large farms. The government has also been unable to target the subsidies more narrowly at small and marginal farmers because of opposition from owners of medium-sized and large farms and logistical problems perceived to be associated with the change. The study also shows that reform of the policy framework for production and distribution of fertilizers has failed because of the presence of a strong coalition consisting of the fertilizer industry, the MoCF, and the MoA, which has successfully argued that policy reform would reduce India's self-sufficiency in fertilizer production and therefore its food security. The advocates for change in policy are fewer and less articulate and consistent in their message. Finally, the reform of fertilizer subsidies has been stymied by the inadequate supply of natural gas in India.